The Code of the City of Atlanta 163-64 (William T. Newman ed., 1879) - (:unkn) unknown (My University, 1879)
Ch. 42-Powder, §§ 459-464: Prohibited merchants from keep more than one keg of powder at a time in any house. Powder shall be kept in a tin can. Violators fined not exceeding one hundred dollars or imprisoned not exceeding thirty days.
Keywords: GUNPOWDER - STORAGE